THE RELATIONSHIP BETWEEN INTERNAL CONTROL, REGULATION AND FRAUD WITH RISK MANAGEMENT AS A MODERATING VARIABLE - Elis Lisnawati; Apollo Apollo (Dinasti Publisher, 2020)
Some Government agencies have a poor strategy in dealing with risk because they consider risk management only a formality. This research aims to determine the relationship of the implementation of internal control, regulation and fraud with risk management as a moderating variable, a case research in the Tangerang City Government. This research is a type of quantitative causal, data collection using a questionnaire to 100 respondents of government officer. Data analysis using SmartPLS. Seven research models partially support hypotheses which are statistically positive and significant effects of the relationship between internal control, regulation, risk management and fraud. except for H? and H? which are statistically negative and weak significant relationship. The result could be used by government as a study material to evaluate the regulation to managing risk in government.